Digital Disintermediation and Efficiency in the Market for Ideas - Christian Peukert; Imke Reimers (Center for Economic Studies and ifo Institute (CESifo), 2018)
Digital technology has allowed inventors to circumvent traditional intermediaries and directly reach consumers, which may affect licensing outcomes and efficiency in the market for ideas. We study these impacts theoretically and empirically in the book publishing industry, where the number of new books available to consumers has almost doubled after the advent of digital self- publishing platforms. Using data on over 90,000 license deals between authors and publishers from 2002 to 2015, we identify disintermediation-related changes in this market from quasi-experimental variation across product types over time. Consistent with digital self-publishing improving an author's bargaining position, we find that authors get substantially more favorable license deals. We further show that ex-ante license fees reflect ex-post demand more accurately. This is consistent with additional entry generating more information about a product type's realized appeal. In markets in which product appeal is difficult to predict, such improvements in the information environment can have large impacts on efficiency and welfare.
Keywords: D22; D83; 330; disintermediation; innovation; book publishing; natural experiment